2021
DOI: 10.1101/2021.12.10.472196
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mitochondrial fission dysfunction alleviates heterokaryon incompatibility-triggered cell death in the industrial filamentous fungus Aspergillus oryzae

Abstract: In filamentous fungi, cell-to-cell recognition is a fundamental requirement for the formation, development, and maintenance of complex hyphal networks. Basically, self/compatible individuals within the fungal species are capable of fusing together, a step important for crossbreeding, which results in the formation of viable vegetative heterokaryons. Conversely, the fusion of incompatible individuals does not result in the formation of viable hyphal networks, but it often leads to growth inhibition or cell deat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…The applicability of such phenotypes to natural systems remains an open question. Recent 11 work by others has shown that, at least in some species, genetically distinct individuals can form heterokaryons under extremely nutrient depleted conditions (Lu et al, 2021;. If this more reduced nutrient context better reflects reality, could it be that nonself recognition is only active when conditions are rich, and that nonself fusions are tolerated in times of trouble?…”
Section: The Regulation Of Fungal Social Interactionsmentioning
confidence: 99%
“…The applicability of such phenotypes to natural systems remains an open question. Recent 11 work by others has shown that, at least in some species, genetically distinct individuals can form heterokaryons under extremely nutrient depleted conditions (Lu et al, 2021;. If this more reduced nutrient context better reflects reality, could it be that nonself recognition is only active when conditions are rich, and that nonself fusions are tolerated in times of trouble?…”
Section: The Regulation Of Fungal Social Interactionsmentioning
confidence: 99%